Produção, circulação e memória de objetos biográficos em um conjunto habitacional paulistano: a vila dos idosos - Silva, Amanda Laurentin [UNIFESP] (2016)
The research intent to analysebiographical objects of elderly?homes that are residents of the housing estate Pari I ?Elderly?s Village Armando Amadeu, by means of aworkfield composed by visits, interviews and photographs, besides, naturally, bibliographic references, as a strategy for understanding the production, circulation and memory of a personal and affective visual system that considers individual and collective trajectories of seniors organized or not in a social movement for housing, the Garmic.